2013
DOI: 10.1063/1.4857495
|View full text |Cite
|
Sign up to set email alerts
|

SnSe2 field-effect transistors with high drive current

Abstract: SnSe2 field-effect transistors fabricated using mechanical exfoliation are reported. Substrate-gated devices with source-to-drain spacing of 0.5 μm have been fabricated with drive current of 160 μA/μm at T = 300 K. The transconductance at a drain-to-source voltage of Vds = 2 V increases from 0.94 μS/μm at 300 K to 4.0 μS/μm at 4.4 K, while the field-effect mobility increases from 8.6 cm2/Vs at 300 K to 28 cm2/Vs at 77 K. The conductance at Vds = 50 mV shows an activation energy of only 5.5 meV, indicating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 13 publications
5
87
2
Order By: Relevance
“…In addition to Mo-and W-based dichalcogenides, several other metal chalcogenides, such as SnSe 2 , GaS, GaSe, In 2 Se 3 , and silicene (a 2D silicon analog to graphene), have also been explored as the channel material for FETs (110)(111)(112)(113). The most recent addition to this exotic class of 2D materials is phosphorene, a single layer of black phosphorus (114)(115)(116).…”
Section: Transition Metal Dichalcogenide Electronicsmentioning
confidence: 98%
“…In addition to Mo-and W-based dichalcogenides, several other metal chalcogenides, such as SnSe 2 , GaS, GaSe, In 2 Se 3 , and silicene (a 2D silicon analog to graphene), have also been explored as the channel material for FETs (110)(111)(112)(113). The most recent addition to this exotic class of 2D materials is phosphorene, a single layer of black phosphorus (114)(115)(116).…”
Section: Transition Metal Dichalcogenide Electronicsmentioning
confidence: 98%
“…[ 13 ] However, most studies have been reported on thick SnSe 2 fi lms obtained by radio-frequency (RF) magnetron sputtering, [ 14 ] or molecular beam epitaxy (MBE) deposition. [ 15 ] Recently reported mechanical exfoliated SnSe 2 crystals demonstrated that it has a high carrier mobility of 8.6 cm 2 V −1 s −1 in ambient environment, [ 16 ] superior to many other reported 2D materials. [ 17,18 ] The layered structure, proper electronic properties, and inherent semiconducting characteristics make SnSe 2 attractive in nanoelectronic and optoelectronic fi elds.…”
Section: Doi: 101002/adma201503873mentioning
confidence: 98%
“…In particular, much progress has been made in characterizing Sn dichalcogenide-based FETs [26, 27]. In 2016, Pei et al .…”
Section: Introductionmentioning
confidence: 99%